Characterization of Myostain (MSTN) and Myogenic Differentiation Antigen (MyoD) and the Effect of Dexamethasone on Their Expression in Large‐Scale Loach Paramisgurnus dabryanus. Issue 4 (8th October 2020) - Du, Zongjun; Wang, Tianzhu; Ming, Wei; Luo, Wei; Xu, Huaming; Lin, Rongnan; Wen, Anxiang
Abstract: Myostatin (MSTN) and myogenic differentiation antigen (MyoD) play an essential role in specification and differentiation of skeletal muscle. However, the role of stress in the regulation of MyoD and MSTN has not been fully revealed and more evidence should be provided. Here, we reported the cloning and expressional analyses of MSTN and MyoD in Large‐scale Loach Paramisgurnus dabryanus (hereafter Pd MSTN and Pd MyoD). Injecting individuals with 0, 60, 600, and 1, 200 μg/kg dexamethasone (DXM) for five consecutive days resulted in a dose‐dependent change of Pd MSTN and Pd MyoD expression. The expression of Pd MSTN was upregulated with increasing DXM concentrations, while Pd MyoD expression was downregulated. The changes in the expression of these genes at different time points for 10 consecutive days were studied after individuals were treated with 600 μg/kg DXM. Compared with the control group, Pd MSTN expression decreased and Pd MyoD expression increased before 12 h, and both Pd MSTN and Pd MyoD expression levels increased at 24 h, which was significantly higher than those in control group. At a prolonged treatment of 5–10 d, expression levels of Pd MSTN and Pd MyoD had significantly reduced. The results indicate that both Pd MyoD and Pd MSTN are involved in DXM‐induced stress in Large‐scale Loach.